2017
DOI: 10.1126/sciadv.1601821
|View full text |Cite
|
Sign up to set email alerts
|

Realization of continuous Zachariasen carbon monolayer

Abstract: Rapid progress in two-dimensional (2D) crystalline materials has recently enabled a range of device possibilities. These possibilities may be further expanded through the development of advanced 2D glass materials. Zachariasen carbon monolayer, a novel amorphous 2D carbon allotrope, was successfully synthesized on germanium surface. The one-atom-thick continuous amorphous layer, in which the in-plane carbon network was fully sp 2 -hybridized, was achieved at high temperatures (>900°C) and a controlled growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 50 publications
1
46
0
Order By: Relevance
“…Among the numerous effects observed one finds: variation (increase or decrease) of electronic conductivity according to the size of the defects, increase of elasticity for moderate density of vacancies and decrease at higher density, decrease of thermal conductance, of fracture strength, enhancement of reactivity, appearance of ferromagnetism and so on [11][12][13][14][15]. As part of this defect engineering activity, a specific effort involving various experimental or numerical techniques -(low pressure) chemical vapor deposition [16], ion/electron irradiation [17][18][19][20][21][22] or molecular dynamic simulation [23][24][25] -has been made toward the design of defect-induced 2D amorphous counterparts of graphene and graphene-like materials. A highlight of this activity is the achievement by electron irradiation of a stepby-step, atom by atom, crystal-to-glass transition giving rise to a vacancy-amorphized graphene structure [16][17][18] similar to the continuous random network proposed by Zachariasen [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the numerous effects observed one finds: variation (increase or decrease) of electronic conductivity according to the size of the defects, increase of elasticity for moderate density of vacancies and decrease at higher density, decrease of thermal conductance, of fracture strength, enhancement of reactivity, appearance of ferromagnetism and so on [11][12][13][14][15]. As part of this defect engineering activity, a specific effort involving various experimental or numerical techniques -(low pressure) chemical vapor deposition [16], ion/electron irradiation [17][18][19][20][21][22] or molecular dynamic simulation [23][24][25] -has been made toward the design of defect-induced 2D amorphous counterparts of graphene and graphene-like materials. A highlight of this activity is the achievement by electron irradiation of a stepby-step, atom by atom, crystal-to-glass transition giving rise to a vacancy-amorphized graphene structure [16][17][18] similar to the continuous random network proposed by Zachariasen [26].…”
Section: Introductionmentioning
confidence: 99%
“…As part of this defect engineering activity, a specific effort involving various experimental or numerical techniques -(low pressure) chemical vapor deposition [16], ion/electron irradiation [17][18][19][20][21][22] or molecular dynamic simulation [23][24][25] -has been made toward the design of defect-induced 2D amorphous counterparts of graphene and graphene-like materials. A highlight of this activity is the achievement by electron irradiation of a stepby-step, atom by atom, crystal-to-glass transition giving rise to a vacancy-amorphized graphene structure [16][17][18] similar to the continuous random network proposed by Zachariasen [26]. Many characteristics of this transition have been determined: the onset of the defect-induced amorphization process, its temperature dependence, the structural response to vacancy insertion, the nature of the electronic density of states of the defective configurations [23], a transition in the fracture response from brittle to ductile when increasing vacancy concentration [27]; finally a careful analysis of the glassy-graphene structure in terms of a proliferation of non-hexagonal carbon rings has been performed [18,25].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have successfully demonstrated the experimental realization of a Zachariasen carbon monolayer employing low-pressure chemical vapor deposition (LPCVD) 32 . Further, disordered graphene has been achieved using alternate methods such as CVD 33 , ion irradiation 16 , 34 , 35 and electron irradiation 36 , 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Cu, Ge exhibits a self-limiting effect resulting from the low carbon solubility in Ge 20 and thus, enables monolayer graphene synthesis 21 . The graphene flakes were reported to nucleate via covalent bonds at Ge dimer vacancies on a surface with (100) crystal orientation 22 .…”
mentioning
confidence: 99%